Bioterrorism in 2001: How Ready Are We? - B Lynn Johnston; John M Conly (Canadian Journal of Infectious Diseases)
On January 30, 2001, the federal Immigration Department's headquarters in Ottawa were evacuated and shut down following a bioterrorism scare, which turned out to be a hoax. The building reopened 48 h later, after it was determined that the substance found was not anthrax (1). In the same week, a similar hoax forced the evacuation of an Ontario provincial government building in Toronto (1).